Mendelian randomization of immune cell phenotypes to discover potential drug targets for B-cell malignancy - Sina A. Beer; Molly Went; Charlie Mills; Codie Wood; Amit Sud; James M. Allan; Richard Houlston; Martin F. Kaiser (Blood Cancer Journal)
Abstract Although treatment options for B-cell malignancies have expanded, many patients continue to face limited response rates, highlighting an urgent need for new therapeutic targets. To prioritize candidate drug targets for B-cell malignancies, we employed Mendelian Randomization to estimate potentially causal relationships between 445 immune cell traits and six B-cell cancers: follicular lymphoma (FL), diffuse large B-cell lymphoma (DLBCL), Hodgkin lymphoma (HL), marginal zone lymphoma (MZL), chronic lymphocytic leukemia (CLL), and multiple myeloma (MM), totaling 22,922 cases and 394,204 controls. 163 traits showed a suggestive association with at least one B-cell malignancy (P < 0.05), with 34 traits being significant after correction for multiple testing (P < 2 × 10−4). By integrating findings with observational data and clinical trial evidence to support drug target candidacy, 24 cell surface markers were identified as druggable targets. In addition to established therapeutic targets such as CD3, CD20 and CD38, our analysis highlights BAFF-R and CD39 in HL, CD25 in MM, CD27 in CLL, CD80/86 in DLBCL, and CCR2 in FL and MZL as promising candidates for therapeutic inhibition. Our findings provide further support for the potential of human genetics to guide the identification of drug targets and address a productivity-limiting step.